Evaluating Schmid criterion for predicting preferential locations of persistent slip markings obtained after very high cycle fatigue for polycrystalline pure copper. (August 2015) - Phung, N.L.; Favier, V.; Ranc, N.
Highlights: Very high cycle fatigue on pure copper polycrystals promotes slip markings of types II and III. Polycrystals modeling assuming crystalline cubic elasticity was carried out. Maximum resolved shear stress criterion predicts the type II slip markings sites. The preferential sites for slip markings are well-oriented twin boundaries. Planes of the primary and cross slip systems emerge at the specimen surface. Abstract: Very high cycle fatigue carried out on pure copper polycrystals promotes early slip markings, labelled as slip markings of types II and III, localized close to grain or twin boundaries. In this work, we focus on whether Schmid criterion can predict the preferential sites of slip markings of types II and III and identify the active slip systems. Combining observations of slip markings and polycrystalline modeling, it is shown that considering pure cubic elastic behavior, maximum resolved shear stress as a criterion for type II slip markings preferential sites is 70% reliable criterion. Concerning slip markings of type III, the reliability falls to 30%. The role of cross slip is highlighted and a scenario rationalizing the stress amplitude conditions and sites to observe early slip markings of type II or III for copper polycrystals is proposed.